Gaps between Evidence and Practice in Postoperative Radiotherapy for Prostate Cancer: Focus on Toxicities and the Effects on Health-Related Quality of Life - Raziee, Hamid; Berlin, Alejandro (Frontiers in Oncology, 2016)
Adjuvant radiotherapy (ART) after prostatectomy for patients with high risk features (extracapsular extension [ECE], seminal vesicle invasion [SVI] and positive margin) has been shown to be associated with improved biochemical disease free survival in three large randomized trials, and with improved overall survival in one. Similarly, salvage radiotherapy (SRT) can effectively achieve biochemical-control in a significant proportion of patients with a rising PSA after surgery. Nonetheless, both approaches of post-operative RT remain highly underutilized. This might be partly due to concerns with overtreatment inherent to adjuvant approaches, and/or hesitance about causing radiation toxicities and their subsequent effects on the patient’s quality of life. Herein, we review the literature lending evidence to these arguments. We show recent series of ART/SRT and their low rates of acute and long-term toxicities, translating only in transient decline in quality of life (QoL) outcomes. We conclude that concerns with side effects should not preclude the recommendation of an effective and curative-intent therapy for men with prostate cancer initially treated with radical surgery.